Development and Validation of an Extractive Spectrophotometric Method for Miconazole Nitrate Assay in Pharmaceutical Formulations - Tadele Eticha; Getu Kahsay; Teklebrhan Hailu; Tesfamichael Gebretsadikan; Fitsum Asefa; Hailekiros Gebretsadik; Boovizhikannan Thangabalan (Journal of Analytical Methods in Chemistry)
A simple extractive spectrophotometric technique has been developed and validated for the determination of miconazole nitrate in pure and pharmaceutical formulations. The method is based on the formation of a chloroform-soluble ion-pair complex between the drug and bromocresol green (BCG) dye in an acidic medium. The complex showed absorption maxima at 422 nm, and the system obeys Beer’s law in the concentration range of 1–30 µg/mL with molar absorptivity of 2.285 × 104 L/mol/cm. The composition of the complex was studied by Job’s method of continuous variation, and the results revealed that the mole ratio of drug : BCG is 1 : 1. Full factorial design was used to optimize the effect of variable factors, and the method was validated based on the ICH guidelines. The method was applied for the determination of miconazole nitrate in real samples.